2020
DOI: 10.21203/rs.3.rs-30320/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of significant disease in a cohort of patients with non-specific enteritis on capsule endoscopy. Clinical suspicion and a high base line Lewis score are predictive of Crohn’s disease.

Abstract: Introduction: As with isolated ileitis the findings of nonspecific small bowel enteritis (NSE) on capsule endoscopy (CE) poses a clinical challenge. There is lack of available evidence to help clinicians to predict significant disease and long-term prognosis.Aim: To define the natural history of NSE in an Irish cohort. Methods: Patients with a finding of NSE were identified from a database. Subsequent investigations, treatments and diagnosis were recorded. Patients were grouped based on ultimate diagnosis: Cro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…A retrospective observational study by Freitas et al 97 investigated 102 patients found to have “isolated terminal ileitis” at ileocolonoscopy, endoscopic abnormalities proximal to the terminal ileum were found in 36.3 % of patients; one third (35/102) were finally diagnosed with CD. Similarly, isolated ileitis on SBCE can frequently herald an ultimate diagnosis of CD, even in patients with an initial negative ileocolonoscopy 98 99 .…”
Section: Crohn’s Diseasementioning
confidence: 99%
“…A retrospective observational study by Freitas et al 97 investigated 102 patients found to have “isolated terminal ileitis” at ileocolonoscopy, endoscopic abnormalities proximal to the terminal ileum were found in 36.3 % of patients; one third (35/102) were finally diagnosed with CD. Similarly, isolated ileitis on SBCE can frequently herald an ultimate diagnosis of CD, even in patients with an initial negative ileocolonoscopy 98 99 .…”
Section: Crohn’s Diseasementioning
confidence: 99%
“…In 88 patients undergoing capsule endoscopy and found to have nonspecific enteritis with scattered small erosions or aphthous ulcers with minimal or mild inflammation, 19% were later diagnosed with Crohn's disease. 6 In another retrospective study of 108 patients with isolated terminal ileitis with a median follow-up time of 54.7 months, 5 (4.6%) developed Crohn's disease after a median of 32.3 months. 7 Another study has shown a progression rate of 14% from isolated ileitis to Crohn's disease, with isolated ileitis cases having excess NOD2 mutations, similar to those with Crohn's disease.…”
Section: Introductionmentioning
confidence: 99%
“…In the capsule study, patients were followed up with endoscopy most commonly, or repeat capsule endoscopy and other small bowel imaging studies, to aid a final diagnosis or the cause for the enteritis. 6 Imaging with barium studies, computed tomography (CT), radiolabeled white cell scans, and visceral angiography have been shown to be useful in defining abnormalities in a single small case series with nonspecific small intestinal ulceration. 11 Applying such techniques to all those with incidental ileal lesions cannot be considered good clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation